Strengthening Cross-Culture of Religion In The Candipuro Lumajang's Ritual of Ruwat Air Tirtosari: A Social Capital Analysis Pierre Bourdieu - Ishari, Nurhafid; Pramuja, Alvin Dian (Proceedings of Annual Conference for Muslim Scholars, 2024)
Conflicts involving religious differences continue to occur in Indonesia. To minimize these problems requires a stronger religious foundation. They conduct a social activity known as ruwat air tirtosari. A cross-religious community in Candipuro village adheres to this ritual as part of their celebration of One Suro. It is part of an effort to strengthen traditional values and social ties by being thankful for abundant water resources. The aim of this research is to investigate how the daily life of Penanggal Village embodies religious harmony. This research method employs qualitative techniques, starting with interviews with local community figures, followed by observations to paint a picture of shared cultural patterns, beliefs, and views within a context of diversity. Interreligious communication uses Pierre Bourdieu's theory of social capital, which does not distinguish between actor roles and structures, to evaluate social interactions. The results of this study imply a deeper balance between religious harmony and local cultural rituals.